Sustainable Development through Household Economics: A Sensory Evaluation of Cakes Produced from Wheat, Cocoyam, Plantain, and Bambara Nut Composite Flour Blends as Functional Snacks - Eunice Kanayo Agidi; Diana Oritsegbubemi Arubayi; Juliana Ego Azonuche (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Composite flours from indigenous crops offer a pathway to healthier snacks, dietary diversity, and reduced reliance on imported wheat, but must meet consumer sensory expectations to be viable. Objective: This study aims to evaluate the sensory properties of cakes made from composite flour blends of wheat, cocoyam, plantain, and bambara nut, and to identify formulations that balance acceptability with functional nutrition potential. Method: An experimental research design was adopted, which allowed for the systematic production and evaluation of cakes prepared from composite flour blends of wheat, cocoyam, plantain, and bambara nut. Result: The sensory evaluation results showed variations in judges’ ratings of cakes made from wheat, cocoyam, plantain, and bambara nut blends compared with 100% wheat cake. Conclusion: These findings support food diversification, partial substitution of imported wheat, and household-scale production through simple SOPs and quality control within the framework of Sustainable Development through Household Economic Units, thereby strengthening local supply chains and micro-business opportunities. Contribution: This study provides empirical evidence that cakes with acceptable sensory quality and nutritional enrichment can promote Sustainable Development through Household Economic Units through simple household-scale SOPs, basic quality control, utilization of local crops, partial wheat substitution, and gender-responsive microenterprises.